Analisis Sistem Penggajian Karyawan pada Perusahaan Waralaba - Zahrani Rahman, AInun; Fajriani, Miftha; Nurafni Oktaviyah (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2023)
Salaries and wages are compensation costs that are routinely incurred in managing the company and are very important, because they are related to employee motivation. This research is a qualitative research with a descriptive approach with case studies. In this study using primary and secondary data sources. This research uses descriptive qualitative research. In this study using primary and secondary data sources. Data collection methods used by researchers are observation, interview and documentation techniques from Indomaret Mapala Branch. Based on the results of the analysis and discussion that have been put forward and linked to the research objectives, the payroll system contained in Indomaret Mapala is divided into several procedures. The procedures that make up the payroll system are recording time and attendance, paying salaries, deductions, bonuses, and overtime.